Pengaruh Body Shaming Terhadap Kepercayaan Diri Siswi Smk Sunan Kalijogo Jabung - Nabila Erica Ristanti; Rindra Risdiantoro (Al-Isyrof: Jurnal Bimbingan Konseling Islam, 2022)
Body shaming affects self-confidence in social interactions, because physical humiliation makes a person feel uncomfortable to the point of embarrassment when he is in society. And makes a person not believe in himself and feel insecure to the point where he can distance himself from his environment. Because Body shaiming can also lead to bullying. In this study, the quantitative method was used, namely a research procedure that produced descriptive data in the form of words and numbers from people or observable behavior. The quantitative approach emphasizes its analysis on numerical data processed using statistical methods via SPSS. Based on the results of the regression test that has been carried out, there is an effect of body shaming on self-confidence in female students at SMK Sunan Kalijogo Jabung, with a closeness correlation in the moderate category. In the results of this study, female students who experienced high body shaming caused themselves to experience insecurity or it could be said that the higher the body shaming, the higher they felt insecure. Based on the results of the study it is known that some students are at a moderate level in Body Shaming, peer social support, self-confidence. Therefore the researchers suggest eliminating the culture of Body Shaming by avoiding making negative comments on one's appearance, because these comments can unknowingly have an impact on one's psychological condition.